Gaming debts of Malaysians in casinos: issues on validity and jurisdiction / Izahairani Izani and Alliff Benjamin Suhaimi - Izani, Izahairani; Suhaimi, Alliff Benjamin (2008)
We discuss the validity of the gambling activities and gambling contracts under Malaysian law. This is because in our opinion, there is some ambiguity in certain Malaysian legislations concerning the validity of both gambling activities and gambling contracts. We also focus on the issues related to the registration of a foreign judgement in the Malaysian courts for the recovery of gambling debts owed by a Malaysian gambler. This is important because the gambler may transcend into different territorial boundaries which would make it difficult to enforce the judgment on that person. This is because there may be multiple jurisdictions involved when the gambler goes to another country after incurring the gambling debts. The purpose of this research is to discover the possible reasons for such ambiguity to exist in the Malaysian legislations. Apart from that, this research is also aimed at determining the proper jurisdiction which will be applicable to the Malaysian gambler when it a claim is made for recovery of that person's gambling debts. We have also made some recommendations that may help avoid any such problems in the future.